INVENTARISASI JAMUR MAKROSKOPIS DI KHDTK (KAWASAN HUTAN DENGAN TUJUAN KHUSUS) UNIVERSITAS LAMBUNG MANGKURAT - Sandra Ayunisa; Dina Naemah; Damaris Payung (Jurnal Sylva Scienteae, 2020)
This study aims to: Finding and analyzing macroscopic mushroom types based on the type, substrate and abiotic parameters found at the observation point in Special Purpose Forest Areas (KHDTK) education and training ULM, for 3 months. The method used in this study is a direct survey in the field by exploring the area arboretum KHDTK education and training ULM. The results of this study note that the macroscopic fungal species found in this study were divided into 2 divisions, 6 classes, 9 orders and 17 families. Macroscopic fungi that were found consisted of Ascomycota and basidiomycota. There are 2 species of macroscopic fungi that are included in Ascomycota, the remaining 34 macroscopic fungal species were found, including the Basidiomycota division. Macroscopic fungi are known that 36 types of macroscopic fungi were found in (KHDTK) education and training ULM, most of the fungus that grows on the substrate of dead and living wood as many as 19 species for dead wood as many as 14 types and fungus that grows on live wood as many as 5 types, while on the ground there are 15 types and grow with 3 types of leaves.Keywords: Diversity, mushroom, substrate, Abiotic parameters